INFLUENCE OF THE AGE OF THE DIAGNOSIS AND THE BEGINNING OF SPECIFIC THERAPY ON MAIN CLINICAL AND LABORATORY MANIFESTATIONS OF A DISEASE IN PATIENTS WITH CYSTIC FIBROSIS - S. A. Krasovskii; N. Yu. Kashirskaya; M. V. Usacheva; E. L. Amelina; A. V. Chernyak; Zh.K. Naumenko ("Paediatrician" Publishers LLC, 2014)
Background: To establish features of a clinical course of a disease at patients depending on age of firstly determine diagnosis of cystic fibrosis. Patients and methods: We examined 130 patients with cystic fibrosis aged under 25 years old. Depending on the age of diagnosis 3 groups of patients were formed: diagnosed at the age of 0-7, 8-18 and 18-25 years old. Results: There were no differences in the main anthropometric, functional, microbiological characteristics and frequency of complications at the age of 25 years between the patients of all three groups. However significant differences in «severity» of genotypes are defined: in group with the diagnosis established at preschool age, «severe» genotypes dominated, in group with the diagnosis established in 7-18 and 18-25 years, - «mild» genotypes. Importance of treatment with dornase alfa in all patients with cystic fibrosis regarding age of establishment of the diagnosis was shown. Conclusion: Early diagnostics determines appropriate beginning of the treatment, which can improve the further prognosis of the disease course. However late diagnostics in patients with «mild» genotype does not have significant influence on the clinical course at the age of 25 years old, which proves protective effects of «mild» mutations.